“Nanotechnology Cancer Asia-Pacific (NCAP) Network” was launched - Tamanoi, Fuyu; Choi, Yongdoo (Quantitative Imaging in Medicine and Surgery, 2012)
The first “Nanotechnology Cancer Asia-Pacific Network” meeting was held on February 15th 2012. Fourteen scientists from the United States (UCLA Jonsson Comprehensive Cancer Center, National Cancer Institute at Frederick, City of Hope), South Korea (National Cancer Center of Korea), China (National Center for Nanoscience and Technology of China, Peking University), Taiwan (Academia Sinica and National Taiwan University), and Japan (Nagoya University and Tohoku University) connected through online conference and discussed openly the current research interests and activities. The meeting was broadcast live enabling web access for other scientist from different parts of the world to participate in our first meeting (Figure 1).